Enhanced Surface Charge Density of Nanogenerators by Small Molecules: A Review. Issue 1 (18th November 2022) - Tayyab, Muhammad; Zhu, Zhiguo; Wu, Bo; Abbasi, Nasir Mahmood; Joseph, Yvonne; Gao, Deqing
Abstract : A triboelectric nanogenerator (TENG) is a promising approach to harvest electric power from the environment by converting mechanical energy into electrical energy. Various nanocomposites and nanofillers are incorporated to enhance triboelectric surface charge density. Researchers recently attempted to incorporate small molecules into TENGs and boost surface charge density after being used in drug delivery and solar cells. However, among the numerous small molecules, the fundamental physics for selecting small molecules has not been reported. Herein, approaches are carefully selected based on small molecules to enhance the surface charge density of the TENG. In addition to that, different surface and bulk approaches are also suggested to incorporate and assimilate small molecules into triboelectric layers. This systematic review provides the historical background, selection mechanisms, and fabrication methods of small‐molecule‐based TENGs to boost the surface charge density. Abstract : Through a variety of surface and bulk manufacturing processes, small molecules can be integrated and infiltrated into triboelectric layers. This thorough review outlines the background, selection criteria, and fabrication processes for small‐molecule‐based triboelectric nanogenerators, which are designed to increase the density of the triboelectric surface charge and effectively capture mechanical energy.